The Role of Parents in Training Deaf Children - Iskandar, Rossi; Supena, Asep (The Center for Disability Studies and Services Brawijaya University, 2021)
The purpose of this study is to find out how parents play in training the speech of deaf children. The research method used is qualitative with library research, namely a series of studies related to library data collection methods, or research objects whose research objects are excavated through various library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents). The results showed that parents have tried to train their children by getting used to talking continuously during learning from home using props and motivating the child to learn. Parents and teachers work together and consult on how to practice speech. The development of sound and rhythm perception communication is a program that is carried out to train the ability of deaf children. But at the time of the covid-19 pandemic parents became special companions as well as teachers while at home to train their children to speak the language daily in addition to being helped through listening aids guided by their teachers.